KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM PENINGKATAN KOMPETENSI PROFESIONAL GURU - Muin, Nurul Amalia; Muin, Putri Nurjayana; Ansar; Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of this study is as follows to describe the mechanism for implementing transformational leadership by the principals of SMKN 3 Bone and SMAN 11 Bone in improving teachers' professional competence. The type of research employed is qualitative. The research design uses an embedded multiple-case study approach. Informants are selected through purposive and snowball sampling. Data collection methods use triangulation. Based on data analysis and discussion, the study concludes that the mechanism for implementing transformational leadership (The Four I's) is adapted to institutional characteristics rather than being uniform. At SMKN 3 Bone, the approach is progressive and technical, fostering a work-oriented culture of innovation. At SMAN 11 Bone, the mechanism is persuasive and administrative; While this ensures teacher compliance with administrative tasks, it does not fully drive transformative learning methods.